A microwave‐assisted synthetic approach to analyzing disubstituted pyrrolo[2, 3‐d]pyrimidine diversity via ligand‐free Cu‐catalyzed N‐arylation. (20th October 2021) - Hong, Chang Sung; Park, Seung Yeong; Byeon, Jeong Seob; Yum, Eul Kgun
Abstract: Facile introduction of diverse substituents to 2‐ or 4‐chloro‐7H‐pyrrolo[2, 3‐ d ]pyrimidines was examined with microwave‐assisted nucleophilic substitution and Cu‐catalyzed N ‐arylation. Microwave‐assisted Cu‐catalyzed N ‐arylation of pyrrolo[2, 3‐ d ]pyrimidines with various nucleophiles proceeded very well with diverse heteroaryl halides. Sequential microwave‐assisted substitution provided good to excellent yields of 2, 7‐ or 4, 7‐disubstituted pyrrolo[2, 3‐ d ]pyrimidines, with short reaction times and energy savings compared with conventional thermal heating. The diverse pyrrolo[2, 3‐ d ]pyrimidine derivatives are useful for screening drug candidates for various diseases. Abstract : A microwave‐assisted synthetic approach to analyzing disubstituted pyrrolo[2, 3‐d]pyrimidine diversity via ligand‐free Cu‐catalyzed N‐arylation